Non-alcoholic Fatty Liver Disease New Insight and Glance Into Disease Pathogenesis - Kang, Ju-Seop (IntechOpen, 2023)
Non-alcoholic fatty liver disease (NAFLD) is characterized by hepatic steatosis that develops in the absence of competing for liver disease etiologies such as alcohol consumption, monogenic hereditary conditions, or iatrogenic causes. The pathogenesis of NAFLD is multifactorial and its understanding is still incomplete. Although knowledge of the cellular and molecular mechanisms underlying disease development and progression has grown signiﬁcantly in recent years, the exact contribution of environmental and genetic factors as well as that of extrahepatic and intrahepatic events in determining the disease phenotype remains ill deﬁned. This book discusses topics highly correlated with NAFLD such as the regulation of iron metabolism, the role of the enzyme heparanase in liver steatosis, transcriptional regulation by ERR and its role in pathogenesis, hepatic lipid homeostasis, therapeutic approaches to NAFLD, and pathogenesis and significance of HDL as a molecular modifier in NAFLD.